Prevalence of Helicobacter pylori and Histopathological Features in Gastric Biopsies from Patients with Dyspeptic Symptoms at a Referral Center in Medellin (2016)
ABSTRACT: Introduction: Helicobacter pylori infection is considered to be the most prevalent chronic infection in the world. It occurs primarily in developing countries. Objective: The main objective of this study was to esti- mate the prevalence of H. pylori infections and gastritis in patients with dyspeptic symptoms who underwent upper endoscopy and correlate endoscopic findings with principal histopathological findings. Methods: We reviewed 2,708 gastric biopsies from patients who had come to the VID Specialized Diagnostic Clinic of the Congregación Mariana in Medellín because of dyspeptic symptoms in 2012 and 2013. Biopsies were studied in the VID Clinical Laboratory of the Congregación Mariana. Histological variables of the results reported by the pathologist were analyzed with statistical methods. Results: The prevalence of H. pylori infection was 36.4%, the average age of infected patients was 46.5 years (SD: 17.1) with a peak prevalence in the group between 40 and 49 years. Prevalence decreased after age 49. The amount of H. pylori was correlated with the intensity of inflammation and activity. The presence of the bacteria was associated with the presence of metaplasia, lymphoid follicles, atrophy and hyperplastic polyps. The intensity of inflammation was associated with the amount of H. pylori and neutrophil activity. Conclusion: The prevalence of H. pylori infection in our study is low compared with other research and exhibited unusual behavior by age group. The amount of H. pylori was correlated with the intensity of inflammation and neutrophil activity.